Kedudukan Hukum Sertipikat Hak Milik Karena Cacat Yuridis Sebagai Bukti Kepemilikan Hak (Studi Putusan Pengadilan Negeri Batusangkar Nomor 67/Pid.B/2021/PN Bsk) - Chanda Ricci; Busyra Azheri; Mulyati, Nani (Universitas Ekasakti, 2023)
One of the plots of land where land registration is carried out by issuing a certificate is Certificate of Ownership Number 00164/Nagari Padang Magek. The certificate is the object of a dispute which has been decided by the Batusangkar District Court Decision Number 67/Pid.B/2021/PN Bsk, which has obtained permanent legal force (inkracht van gewijsde). Based on the Decision of the Batusangkar District Court Number 67/Pid.B/2021/PN Bsk, the issuance of Certificate of Ownership Number 00164/Nagari Padang Magek, namely a Statement of Physical Control of the Field and a Certificate of Land Ownership Number 074/SK/PMT/2000, is a fake document. So the Certificate of Ownership Number 00164/Nagari Padang Magek has a legal defect. The formulation of the problem examined in this research is: 1) what is the legal position of a certificate of ownership due to juridical defects as proof of ownership of rights?; 2) what are the legal consequences of ownership of land rights following the Batusangkar District Court Decision Number 67/Pid.B/2021/PN Bsk? The research method that the author uses is normative juridical, with a case approach. The type of data used is secondary data, which consists of primary, secondary and tertiary legal materials. The data collection technique used is document study. The results of the author's findings are the position of Ownership Certificate Number 00164/Nagari Padang Magek, which has changed the data on the certificate above to become Ownership Certificate Number 1892/Nagari Padang Magek, Land Plot Identification Number 03.10.03.02.01654, with Measurement Letter Number: 2616/2021 dated 27 April 2021, area 940, in the names of Tisra Juwita and Hasni Wirda, still valid and valid. The next finding is that in the Batusangkar District Court Decision Number 67/Pid.B/2021/PN Bsk, the basis for issuing the certificate used was a fake letter related to the ages of the parties, namely Tisra Juwita and Hasni Wirda, not a fake regarding the subject of their rights. So the plot of land registered in Certificate of Ownership Number 00164 is still legally valid in the names of Tisra Juwita and Hasni Wirda. Certificates issued based on fake documents can be canceled by submitting a written application to the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency through the Head of the Land Office where the object is located, in this case the Head of the Tanah Datar Regency Land Office.